Needs analysis: An interactive e-assessment for basic design graphic course - Azhariyah, Sari; Ambiyar, Ambiyar (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This research aims to describe the results of the needs analysis in the process of developing e-assessment media on the basic graphic design course. This research was a qualitative descriptive research by using survey methods in identifying the needs of students and teachers in learning assessment. In this research, the needs analysis related to the achievement of the student learning outcomes, the problems faced by the students and the media needed by students in the learning assessment process. This research used a questionnaire given to 32 students of grade X and 2 teachers of the basic graphic design subject. The results showed that: 1) there was still lack of assessment media that can be used as an independent assessment for students; 2) android-based interactive assessment media was needed on the basic graphic design subject. Based on these findings, it can be concluded that students need an interactive assessment media that can be used as an independent assessment media. In addition, these findings will be used in designing interactive e-assessments in basic graphic design subject.